PENGARUH KEMAMPUAN TENAGA MEDIS TERHADAP PELAYANAN KESEHATAN DI RUMAH SAKIT BUDI MULIA KOTA BITUNG - KAWULUR, NADIYA; POSUMAH, JOHNNY HANNY; TAMPONGANGOY, DEISY (JURNAL ADMINISTRASI PUBLIK, 2020)
medical personnel to provide health services. the problem that must be considered here is the lack ofefficiency, effectiveness and professionalism in overcoming the problems that exist in Rs Budi Mulia,Bitung City. The still weak ability of medical staff to make plans for health services and their behavior inanticipating health problems that occur is apparently not in accordance with community expectations.Medical personnel must have high performance and pay attention to service quality. The quality of medicalpersonnel is the level of excellence expected for service at the level of excellence to meet demands. Thequality of service depends on the ability to provide services to the ability to provide services to meetexpectations in Rs Budi Mulia, Bitung City. The method used is quantitative meode. While the data analysistechnique used is simple linear analysis to test the effect between variables and correlation analysis. Basedon research conducted and continued by analyzing the data obtained, it means that the ability of medicalpersonnel has a positive correlation to health care and that the ability of medical personnel has adetermining power or influence on health services in Rs Budi Mulia, Bitung City.Keywords: the influence of the ability of medical personnel, health services